What makes honours programmes attractive in the eyes of teaching and nursing students? - Helle Mathar; Nina Troelsgaard Jensen; Niels Sandholm Larsen (Journal of the European Honors Council, 2024)
Since honors programs are a novelty in the Danish educational system, knowledge is needed on what makes the honors attractive to the students. The aim of this study was to provide insight into the motivation of second year students applying for nursing and teaching honors programs. The approach draws upon the work of Vincent Tinto and Albert Bandura. A content analysis based of student applications to the programs showed that both groups find the content of the programs attractive. In their applications teaching students stressed having extraordinary skills within the cognitive domain, while nursing students emphasised having skills within the affective domain. Both groups had the expectation that an honors program would facilitate their pursuit of personal and professional goals. Becoming a part of a community of likeminded peers was an attraction. Joining honors program represents a strategy to persist and complete one’s degree, which means the programs may help to retain the group of extraordinary, ambitious students.